(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The high prevalence of pathology of the upper digestive tract among the child population is an important and urgent social and medical problem. The number of children with chronic inflammatory diseases of the digestive system is growing. The upper section digestive tract pathology begins in preschool and school age very often. The prevalence of children with the upper section digestive tract pathology, the characteristics of the course, the high risk of the early disability, among which the gastro-duodenal pathology is the central place, it is the actual problem of the day. It actualizes scientific development in searching the most effective diagnostic measures, etiotropic and pathogenetically substantiated therapy, rehabilitation and prophylaxis of this common pathology actual. The author notes that chronic gastro-duodenitis is extremely rare in the form of mono-disease. Humoral and cellular immunity links changes contribute to transition of the disease to unfavorable or complicated variants. The article considers etiology, pathogenesis, diagnostics and modern treatment methods of this pathology. It describes course and characteristics of the disease at concurrent pathology.